FINTECH INNOVATIONS: EXPLORING THE LATEST TECHNOLOGICAL ADVANCEMENTS AND THEIR IMPACT ON THE BANKING AND FINANCIAL SECTOR - Abdusadiqov Zohidjon Olimjon o’g’li (Лучшие интеллектуальные исследования, 2023)
Abstract: This comprehensive article delves into the dynamic landscape of fintech, focusing on the transformative impact of blockchain technology, digital currencies, and online payment systems in the banking and financial sector. By examining the implications of these technological advancements, the article highlights the opportunities and challenges presented by the integration of fintech innovations, emphasizing the need for proactive regulatory measures and collaborative initiatives to ensure responsible and sustainable financial development.